Association of Aortic Phenotypes and Mechanical Function With Left Ventricular Diastolic Function in Subjects With Normally Functioning Bicuspid Aortic Valves and Comparison to Subjects With Tricuspid Aortic Valves - Lee, Soo Youn; Shim, Chi Young; Hong, Geu-Ru; Seo, Jiwon; Cho, Iksung; Cho, In Jeong; Chang, Hyuk-Jae; Ha, Jong-Won; Chung, Namsik (The American journal of cardiology, 2015)
A bicuspid aortic valve (BAV) is often associated with dilation or aneurysm of the ascending aorta (AA) despite of absence of significant valve dysfunction. Bicuspid aortopathy and consequent aortic stiffness may adversely affect left ventricular (LV) diastolic function. This study aimed to investigate the impact of global and regional aortic mechanical function on LV diastolic function in subjects with BAV. Fifty-six subjects with BAV (45 men, mean age 52 ± 13 years) without significant valve dysfunction and 56 age- and gender-matched controls with tricuspid aortic valve were studied. The aortic phenotypes were classified into 3 groups: normal shape, predominant dilatation of the sinus of Valsalva, and predominant dilatation of the AA. Structural and functional parameters of the AA and LV were measured using 2-dimensional echocardiography. Global aortic mechanical function was assessed by radial artery tonometry. The subjects with BAV showed a higher incidence of a predominant AA phenotype (53.6% vs 17.9%, p <0.001), larger indexed aortic diameters, increased augmentation index, lower pulse pressure amplification, lower early diastolic mitral annular (e’) velocity, and higher E/e’ than those with tricuspid aortic valve . The e’ velocity and E/e’ varied with different aortic phenotypes in subjects with BAV. Correlations between e’ velocity and parameters of aortic stiffness were stronger in subjects with BAV than those in controls. Multiple regression analysis revealed that augmentation index normalized for a heart rate of 75 beats/min was an independent determinant of e’ velocity (β = −0.24, p = 0.044) and E/e’ (β = 0.30, p = 0.018) in subjects with BAV even after controlling for confounding factors. LV diastolic function is closely related to aortic phenotype and mechanical alteration in subjects with BAV.